La estadística en los medios de comunicación como detonante del miedo en estudiantes Universitarios Colombianos - Riaño-Vargas, Angie; Rocha-Salamanca, Pedro (Revista Científica, 2020)
The article will present some results related to the study and understanding of the bias of availability in the field of Statistical Education from a critical social perspective. A research tool consisting of a set of questions about the fears of university students regarding climate change was designed and applied in a control and treatment group, social security, economic stability, violence, and insecurity; which can be exacerbated by the media.